(untitled) (International Seven Journal of Multidisciplinary, 2023)
It is known that the preparation of the surgical patient in his nutritional context brings clear results regarding the postoperative evolution. Such knowledge, already based on the literature, gains even more emphasis when a population cut is made from the perspective of cancer patients, thus, good postoperative nutritional management is necessary. For this work, an integrative systematic review based on six steps was chosen. We chose to use the PICOT method, formulating the question to be answered in this review: "Is it possible to perform clinical and nutritional measures in the postoperative period to assist the adult oncology patient in recovering from the surgical procedure, reducing the number of complications and length of hospital stay?" For the temporal cut-off of this work, articles published between the years 2013 and 2023 were used. In addition, for the choice of articles, texts in English and Portuguese were selected. After pre-selection and selection by applying the inclusion and exclusion criteria, twenty-nine (29) articles were identified, of which two (2) are systematic reviews, four (4) observational studies, one (1) prospective qualitative studies, fifteen (15) controlled clinical trials, and seven (7) meta analyses. The literature supports that early recovery of oral diet, even at low initial rates (daily energy sufficiency >25%), improves nutritional status as well as reduces mortality. Another alternative presented by studies for the definition of feeding routes is the definition of enteral tube insertion. Although it is not preferable, because one should always seek the food route closest to the physiological one, parenteral nutrition is often necessary. Postoperative nutritional supplementation, both parenteral and enteral, with polyunsaturated fatty acids (PUFA), such as omega-3, associated with amino acids such as glutamine and arginine, has shown statistical relevance in reducing secondary infectious complications in the postoperative period. Studies still differ on the reduction in mortality compared to standard enteral nutrition. More robust studies may be needed to rule out or impose such a nutritional supplementation practice. There is still an attempt to supplement total protein in oral and enteral diets in an attempt to improve postoperative recovery. The association of a high protein diet in the immediate postoperative period with the concomitant use of dietary fiber (Fructooligosaccharide dietary fiber) has also been studied. The number of patients with late diagnosis in advanced oncologic stages is still a worrisome reality, especially after the advent of COVID-19. Postoperative care for nutritional rehabilitation lacks more robust studies to indicate with greater certainty a general management protocol. immunomodulation therapies may show good response when used in the postoperative period.